Exploring EFL Teacher's Reflective Practice toward Autonomy-Supportive Instructional Behavior in EFL Context - Roki'ah, Siti; Sumardi, Sumardi; Suparno, Suparno (Universitas Hamzanwadi, 2023)
This study explores teachers' reflective practices on instructional behaviors supporting autonomy in EFL classroom teaching. This study used the narrative inquiry method, where the researcher used teacher’s stories based on their experiences as data. Participants in this study were purposively selected based on the numerous of teaching experience in the EFL context. Semi-structured interviews and classroom observations were conducted to collect data. The data were analyzed through interactive model analysis. The finding shows that the higher level of education the less Autonomy-supportive instructional behavior was implemented by the teacher since the teacher considered that the higher a student’s level of education, the more they have the capability to determine their learning. While ASIB (Autonomy-supportive instructional behavior) highly influence on student satisfaction, it influences student motivation and a slight effect on student academic achievement for tertiary level. The differences in the implementation of ASIB should focus on pedagogical strategies that appropriate implemented in certain level of education rather than eliminating some ASIB because teachers think certain levels of education do not need autonomy support in learning.